Design and development of educational multimedia for second grade: systematization of an experience (Revista Electrónica Calidad en la Educación Superior, 2019)
The systematization of the process of developing an educational technology resource that aimed to solve the problem of fluency and reading comprehension of the second grade group of the Coope Rosales School of Quircot de Cartago is presented. The guiding question of this work was the following: how to favor and, at the same time, increase fluency and reading comprehension in second grade students of Coope Rosales School in Quircot de Cartago, through the design and development of a multimedia resource? At the end of the intervention, an interactive educational multimedia of exercise and practice was obtained that allows to improve the fluency and reading comprehension of the target population, as a complement to the didactic strategies implemented by the guide teacher in the Spanish lessons. The article is relevant to the quality of education because it describes a successful production process consisting of three stages: design, implementation and evaluation, which can be replicated by other people interested in solving educational problems through educational technology.
Keywords: Educational technology; multimedia educativo; educational resource; fluency and reading comprehension